2022
DOI: 10.1021/acs.jafc.1c07730
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of Plant Dietary miRNAs Starts in the Mouth under the Protection of Coingested Food Components and Plant-Derived Exosome-like Nanoparticles

Abstract: The regulatory functions of plant miRNAs on mammalian bodies are controversial, mainly because stability of the miRNAs in the digestive tract, as the prerequisite for their cross-kingdom effects, has somehow been overlooked. Hence, as the first stage of food ingestion, stability of plant miRNAs in human saliva has been investigated. The results show that plant miRNAs are of considerable resistance against salivary digestion, as surviving miRNAs more than 20 fM are detected. The stability varies dramatically, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 52 publications
0
28
0
1
Order By: Relevance
“…However, a certain amount of miR159 (1.5 fM) survived after being in rat blood for 4 h. This agreed with the previous reports that miR159 was able to withstand RNase digestion under unfavorable oral and gastrointestinal conditions. 47 , 48 The quantification of miR159 by miRCURY was undesirable in terms of sensitivity and dynamic range. The method failed to detect the presence of miR159 after the injection for 2 h ( Figure 6 A), and the valid dynamic range (R 2 = 0.9871) only covered five orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…However, a certain amount of miR159 (1.5 fM) survived after being in rat blood for 4 h. This agreed with the previous reports that miR159 was able to withstand RNase digestion under unfavorable oral and gastrointestinal conditions. 47 , 48 The quantification of miR159 by miRCURY was undesirable in terms of sensitivity and dynamic range. The method failed to detect the presence of miR159 after the injection for 2 h ( Figure 6 A), and the valid dynamic range (R 2 = 0.9871) only covered five orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…6,8,10 Although the regulatory effects are still in debate, our recent findings showed that miR159 was of superior stability under the digestive conditions. 15,16 Chapado et al reported that the broccoli-derived miRNAs could survive common foodprocessing practices such as boiling, frying, microwaving, and steaming. Complete elimination of the miRNAs was not observed after the in vitro digestion stimulating oral, gastric and intestinal conditions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our recent works show that some plant miRNAs are able to resist the digestion and are absorbed by Caco-2 cells (a model cellline for intestinal epithelial cells). 15,16 Among them, bol-miR159 was observed with the highest stability and absorption efficiency, suggesting its presence in intestines of recipients and appreciable bioavailability. In 2016, Liu et al conducted a pioneering study exploring the cross-talk between gut microbiota and host miRNAs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this regard, recent animal model research discovered that plant microRNAs in their free form could be absorbed in the stomach through an SIDT1-dependent mechanism . Moreover, it has been demonstrated that the digestion of ingested microRNAs starts in the mouth by RNases present in the saliva and that the food matrix plays a key role in protecting their degradation by encapsulating the microRNAs with food components during mastication . Most microRNAs in fruits and vegetables are contained in exosome-like nanoparticles, which also protect microRNAs from degradation by RNases in the mouth.…”
Section: Dietary Micrornas: Do Humans Absorb Them?mentioning
confidence: 99%